The Correlation of Vocabulary Mastery and Students’ Reading Comprehension - Nurhayati, Marlinda; Apriliyanti, Dewi Listia (IKIP Siliwangi, 2025)
This study pursuits to have a look at the relationship among vocabulary mastery and reading comprehension of class eleventh grade students. The approach used on this examine is a quantitative research method with a correlational design. This examine used vocabulary mastery test and analyzing comprehension test as instruments to collect data. Before testing the relationship between the two variables, a normality test was conducted. The results showed that the data were normally distributed so that the analysis continued statistically using Pearson Product Moment. While the Pearson correlation reached a point of 0.896 which means the correlation between the two is very large. Regarding the results of the study, it concluded that vocabulary mastery has a positive contribution to reading comprehension. In other words, that vocabulary knowledge has influenced in selecting some reading comprehension teaching methods.